Pemberdayaan Ibu Balita dalam Mengenali dan Mencegah Diare di Desa Bangun Rejo Tanjung Morawa Deli Serdang (Lembaga Pengembangan Kinerja Dosen, 2025)
Diarrhea is still the leading cause of infant morbidity and mortality in Indonesia, especially in areas with limited access to clean water and adequate sanitation. This community service activity is carried out with the aim of increasing maternal knowledge about the signs and symptoms of diarrhea in children, increasing maternal awareness in maintaining children's hygiene and health to prevent diarrhea, and providing practical training on early treatment of diarrhea. This activity involved 30 mothers who have early childhood in Bangun Rejo Village, Tanjung Morawa District. The methods used include interactive lectures, group discussions, demonstrations of making oralite solution (ORS), correct handwashing practices, and distribution of educational leaflets. Evaluation was carried out through pre-test and post-test to measure the increase in participants' knowledge before and after the activity. The results of the activity showed a significant increase in maternal understanding of the prevention and treatment of diarrhea. Participants were able to identify early symptoms of diarrhea, practice how to make ORS correctly, and show readiness to take the child to a health facility if signs of dehydration appear. This activity proves that community-based health education is effective in increasing maternal knowledge and preparedness in preventing and treating diarrhea in children. Strengthening similar educational programs is essential to be implemented sustainably, especially in areas with a high risk of diarrheal diseases. These efforts can make a real contribution to reducing the incidence of diarrhea and improving the health status of children in vulnerable communities.